Ideal Standards, Acceptance, and Relationship Satisfaction: Latitudes of Differential Effects - Buyukcan-Tetik, Asuman; Campbell, Lorne; Finkenauer, Catrin; Karremans, Johan C.; Kappen, Gesa (Frontiers in Psychology, 2017)
We examined whether the relations of consistency between ideal standards and perceptions of a current romantic partner with partner acceptance and relationship satisfaction level off, or decelerate, above a threshold. We tested our hypothesis using a three-year longitudinal data set collected from heterosexual newlywed couples. We used two indicators of consistency: pattern correspondence (within-person correlation between ideal standards and perceived partner ratings) and mean-level match (difference between ideal standards score and perceived partner score). Our results revealed that pattern correspondence had no relation with partner acceptance, but a positive linear/exponential association with relationship satisfaction. Mean-level match had a significant positive association with actor's acceptance and relationship satisfaction up to the point where perceived partner score equaled ideal standards score. Partner effects did not show a consistent pattern. The results suggest that the consistency between ideal standards and perceived partner attributes has a nonlinear association with acceptance and relationship satisfaction, although the results were more conclusive for mean-level match.